A Demand Determinants Model for Public Spending in Spain - Jaén-GarcÃa, Manuel (International Journal of Economics and Financial Issues, 2017)
In this paper an attempt is made to analyze the causes of growth of public government considering a demand model. The main contribution is the elaboration of a comprehensive and synthetic model in which economic-structural and political-institutional variables are included. To our knowledge, it is the first work that attempts this kind of model as it considers such a high number of variables, which implies great difficulties upon conducting the corresponding analysis. We consider the public expenditure in Spain in the period 1958-2014 where there are structural points. Then we use unit root and cointegration tests in a structural breaks context. Keywords: Government Spending, Demand Determinants Model, Cointegration, Structural Breaks JEL Classifications: H11, H50, E62